ANALYSIS OF THE OPTIMAL NUMBER OF STAFF NEEDED USING WORKLOAD INDICATOR OF STAFFING NEEDED (WISN) METHOD IN LABORATORY UNIT OF PUBLIC HOSPITAL ANUTAPURA PALU - Napirah, Muh. Ryman; Sulistiani, Andi Okki (YCAB Publisher & IAKMI SULTRA, 2015)
Background: The amount of labor in the laboratory unit hospital of Anutapura Palu workforce was 30 people, but there were still problems in terms of inspection of samples that only consisted of some people in a kind of examination while in terms of inspection of the sample was in need of power because the large number of visits from patients who require to carry out an examination of sample. One of manpower planning method is Workload Indicator Of Staffing Needed (WISN) that calculated the optimal amount based on workload of employees.Objective: This study aimed at finding out of the optimal number of staff needed in The laboratory unit at RSU Anutapura using WISN method.Methods: This study was a quantitative study with descriptive approach. Data were collected using work sampling method, observation, and document review.Results: It showed that using productive time of the activities time total was 88,51% and using productive time of working hours was 114,240 minutes per year, workload standard is 5817.32 per year and the loose standard is 0,4 per year.Conclusion: Based on the analysis of the optimal number of staff needed using WISN method, it can be concluded that the laboratory unit still needs 8 people, and for manpower planning, things that need to consider are qualification and competence to get a good quality of labor.